IDENTIFIKASI PEMAHAMAN KONSEP SISWA SMP/MTs PADAMATERI GERAK MENGGUNAKAN THREE-TIER TEST - Fita Fatimah (Education Journal : Journal Educational Research and Development, 2017)
This study aims to determine the profile of students' understanding concept of SMP/MTs on the material of motion. Do students really understand the concept given, or have experienced the lack of knowledge and even misconceptions so can be followed up with improvements in the learning process to overcome the problem. This research was conducted by giving the motion material test to the students of class VII SMP/MTs in Jember by using ThreeTier Test. Three-tier test is a multi-tiered, multi-choice written test. First tier problem that serves to assess the students' descriptive knowledge and second tier questions in the form of points of reason for the answers to the first level question that serves to assess the mindset of students. The second level consists of four answer options, then the two tier test is added with the Confidence Rating (confidence level) with two answer options, which are sure and unsure. The two-tier test combined with the Confidence Rating is then called the Three-tier Test. Based on the data obtained found 13.2% of students already understand the concept of motion materials, 14.4% of students are still less understood about the material motion, and 57.4% of students experience misconception in the material motion.